A combined chemical/size fractionation approach to study winter/summer variations, ageing and source strength of atmospheric particles. (October 2019) - Canepari, S.; Astolfi, M.L.; Catrambone, M.; Frasca, D.; Marcoccia, M.; Marcovecchio, F.; Massimi, L.; Rantica, E.; Perrino, C.
Abstract: We studied the size distribution of ions (Cl −, NO3 −, SO4 =, Na +, NH4 +, K +, Mg ++, Ca ++ ) and elements (As, Ba, Cd, Co, Cs, Cu, Fe, Li, Mn, Ni, Pb, Rb, Sb, Se, Sn, Sr, Ti, Tl, V, Zn) during the winter and summer seasons of seven consecutive years (2008–2014) in an area of the Po Valley (Northern Italy) characterised by industrial, agricultural and urban settings. The study included the collection and analysis of 41 series of size-segregated samples (MOUDI sampler, 10 stages, cut sizes from 0.18 to 18 μm). Ions were analysed by ion chromatography; elemental analysis was carried out by ICP-MS, by applying a chemical fractionation method able to increase the selectivity of PM source tracers. Our results indicate that important winter/summer variations occurred in both the concentration and size distribution of most PM components. These variations were explained in terms of variations in the strength of the prevailing sources of each component. The contribution of biomass burning for domestic heating was highlighted by the well-known tracer K + but also by the soluble fraction of Rb, Cs and Li. Biomass burning contribution to atmospheric PM was mostly contained in the fine fraction, with a broad size-distribution from 0.18 to 1.8 μm. This source also appreciably increased the concentration of other elements in fine PM (As, Cd, Co, Mn, Pb, Sb, Sn). A few PM components (tracers of sea-spray, brake lining and some industries) did not show marked seasonal variations in concentration and size distribution. However, during winter, for brake lining and industry tracers we observed an upward shift in the dimension of fine particles and a downward shift in the dimension of coarse particles, due to the ageing of the air masses. Graphical abstract: Image 1 Highlights: The concentration and size distribution of PM components show seasonal variations. Combination of size and elemental fractionation improves the selectivity of tracers. K + and the extracted fraction of Rb, Cs and Li are good tracers of biomass burning. The concentration of several toxic elements is influenced by biomass burning. We observe changes in particle dimensions resulting from ageing of the air masses.